Sistema para la protección de cultivos soterrados y terrestres contra las heladas en la Sabana de Bogotá para el año 2050 - Castellanos Mestizo, Cesar Camilo (Universidad Antonio Nariño, 2021)
The havoc that climate change is causing due to the increase in greenhouse gases is irreversible, temperature changes have become increasingly extreme and have reached levels never before recorded; Gradually, this phenomenon has been affecting the country and although for many its evidence is not so remarkable, different sectors such as agriculture and livestock have suffered damages that have decreased production, consequently, economic losses especially for small and medium producers located in rural areas, as a result of this there are increases in prices and deterioration in the quality of the final product.